Diplomasi Indonesia dalam Menangani Kasus Perdagangan Manusia di Kamboja - Cyndi Ardanya; Meylinda Ekalia Wulandari; Kustiawan (Indo Publishing, 2025)
This article examines Indonesia’s diplomatic efforts in addressing human trafficking cases in Cambodia, with a focus on protecting Indonesian citizens (WNI) who are victims of cross-border exploitation. The study employs a descriptive qualitative method using a literature review, analyzing scholarly journals, books, official reports, and reliable online sources on human trafficking and international diplomacy. Findings indicate that Indonesia’s diplomacy plays a strategic role through bilateral and multilateral mechanisms, including the signing of Memoranda of Understanding (MoUs) with the Cambodian government, cooperation within ASEAN forums, and collaboration with international organizations such as Interpol, IOM, and ILO. Indonesia has also strengthened migrant worker protection through the Indonesian Migrant Worker Protection Agency (BP2MI), improved transparency in migration processes, and provided law enforcement training. Interpol Indonesia contributes significantly to accelerating victim identification and apprehending transnational criminals. These diplomatic initiatives function not only as foreign policy instruments but also as means to protect human rights, effectively enhancing legal protection, expediting victim repatriation, and reducing human trafficking in Southeast Asia, particularly in Cambodia.